Homebuyer complaints during defect liability period: Critical analysis of individual presumptions, defect discovery and post-rectifications factors - Mohd Saufi, .; Liyana, Mohamed Yusof; Rahimi, A. Rahman (Emerald Publishing Limited, 2024)
Purpose: This study aims to investigate factors leading to homebuyer complaints during defect liability periods (DLP). The specific study objectives are to: identify critical factors leading to homebuyer complaints during DLP; compare the factors among regions, house price and developer recognition; group the factors into subcategories; and evaluate the criticality of the categories. Design/methodology/approach: A systematic literature review and semi-structured interviews with 20 homebuyers were carried out, generating 37 factors. A survey was developed with the factors categorized into three categories: individual presumptions, defects discovery and post-rectifications. The survey data were collected from 104 homebuyers who had acquired new houses within the last five years. The collected data were subjected to statistical analyses, including normalized mean analysis, Kruskal–Wallis H test, factor analysis and fuzzy synthetic evaluation. Findings: The results indicate that individual presumptions, defects discovery and post-rectifications have 8, 14 and 6 critical factors. Then, there are high similarities in the criticality of the factors among regions, house price and developer recognition. The defect discovery factors can be grouped into function- and precision-related factors. Finally, the defect discovery category has the highest overall criticality, followed by post-rectification and individual presumption categories. Originality/value: To the best of the authors’ knowledge, this study is the first to quantitatively investigate factors leading to homebuyers’ complaints during DLP. The study findings offer a new perspective for policymakers in the development of housing regulations.